CNC handbook - Kief, Hans B. 4 0 16; Roschiwal, Helmut A.,;Hood, Jefferson B.; 5 (New York : McGraw-Hill, 1999)
Gain a thorough understanding of computer-based numerical control systems, components, and technologies. Featuring hundreds of color images and schematic diagrams, CNC Handbook explains machining fundamentals and shows you how to build and safely operate fully automated, technically sophisticated mechatronic equipment. Learn how to work with position controllers, accomplish rapid and precise machine motions, use CAD and CAM systems, and integrate CNC into IT networks. The latest CNC programming languages, flexible manufacturing systems, and troubleshooting methods are also discussed in this hands-on guide.--Back cover.
Translated from German.;Includes index.
Keywords: 2 -- 0; 6; Machine-tools - Numerical control.;Machine-tools - Numerical control - Programming.;Machine shops - Automation.;Computer programming; 20; 2